2020
DOI: 10.5194/os-16-1225-2020
|View full text |Cite
|
Sign up to set email alerts
|

Properties and dynamics of mesoscale eddies in Fram Strait from a comparison between two high-resolution ocean–sea ice models

Abstract: Abstract. Fram Strait, the deepest gateway to the Arctic Ocean, is strongly influenced by eddy dynamics. Here we analyse the output from two eddy-resolving models (ROMS – Regional Ocean Modeling System; FESOM – Finite-Element Sea-ice Ocean Model) with around 1 km mesh resolution in Fram Strait, with a focus on their representation of eddy properties and dynamics. A comparison with mooring observations shows that both models reasonably simulate hydrography and eddy kinetic energy. Despite differences in model f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 63 publications
(88 reference statements)
10
23
0
Order By: Relevance
“…We have confirmed the presence of two recirculation pathways at 78 inate in the WSC and are advected by the mean flow of the recirculation branch, or that they originate in the recirculation branch itself, provided it is subject to similar instabilities. We may also observe self-propagating eddies with a westward propagation speed, as suggested by previous studies (Wekerle et al, 2020;Bashmachnikov et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…We have confirmed the presence of two recirculation pathways at 78 inate in the WSC and are advected by the mean flow of the recirculation branch, or that they originate in the recirculation branch itself, provided it is subject to similar instabilities. We may also observe self-propagating eddies with a westward propagation speed, as suggested by previous studies (Wekerle et al, 2020;Bashmachnikov et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…(Hattermann et al, 2016). Consistently, in two eddy resolving models, Wekerle et al (2020) found the main generation region…”
Section: Seasonal Variabilitysupporting
confidence: 63%
See 2 more Smart Citations
“…These growth-rate estimates do not take into account potential losses due to grazing by zooplankton or viral lysis, and thus represent rather the lower time limit. Based on this we hypothesize that, at the time of sampling, the age of the observed filament was already at least 10 d. Although temporal dynamics are not resolved by our sampling strategy, the approximated lifetime matches recent estimates of mesoscale eddies lifetime in Fram Strait based on high-resolution ocean-sea ice models (Wekerle et al 2020). The boundaries of these mesoscale eddies may harbor submesoscale filaments such as the one studied here.…”
Section: Discussionsupporting
confidence: 75%